Finasteride Topical Delivery Systems for Androgenetic Alopecia - Khan, Muhammad Z.U.; Khan, Shujaat A.; Ubaid, Muhammad; Shah, Aamna; Kousar, Rozina; Murtaza, Ghulam (Current Drug Delivery, 2018)
Androgenetic alopecia, generally recognized as male pattern baldness, is a gradually developing medical and physiological change, which is manifested by continuous hair-loss from scalp. Finasteride (4-aza-3-oxosteroid) is a potent anti-baldness compound that selectively and competitively inhibits the 5α-reductase isoenzymes. Prolonged oral use of finasteride leads to the emergence of sexual disorders including decrease in libido, gynecomastia, erectile dysfunction, ejaculation disorder, orgasm disorders and mood disturbances. Since, hair follicles widely home in 5α-reductase, topical formulations of finasteride in comparison to its oral formulations are expected to potentially reduce its systemic adverse effects. The analysis of literature has revealed some delivery systems developed for the enhanced and localized penetration of finasteride into the skin. These finasteride delivery systems include polymersomes, vesicular nanocarriers, vesicular ethosomal carriers, liposomes and niosomes, liquid crystalline nanoparticles, topical solutions and gels. The aim of this review article is to briefly amass all literature on topical delivery of finasteride to elaborate best dosage form, i.e. formulation having maximum permeation rate. This study will serve as a future perspective regarding topical delivery of finasteride. The literature analysis has exhibited that most of the previous investigators have used propylene glycol in their finasteride-loaded topical formulations, while poloxamer P407, monoolein, transcutol P and choline was used in few formulations. Moreover, among all drug delivery systems, finasteride liposomal gel system consisting of 2% methyl cellulose and gel system containing poloxamer P407 exhibited the highest flux with a value of 28.4 ± 1.3 μg/cm2h and 23.1 ± 1.4 μg/cm2h, respectively. Several topical drug delivery techniques such as topical microneedles, aerosol foams, nanoemulsions, microsponges, and emulsifier free formulations, fullerenes, ointments, pastes, creams, gel and lotions are still to be worthy regarding finasteride topical delivery in future.
Keywords: Finasteride